Clinical, Biochemical, and ATR-FTIR Spectroscopic Parameters Associated with Death or Survival in Patients with Severe COVID-19 - Martinez-Cuazitl, Adriana; Mata-Miranda, Monica M.; Sanchez-Brito, Miguel; Valencia-Trujillo, Daniel; Avila-Trejo, Amanda M.; Delgado-Macuil, Raul J.; Atriano-Colorado, Consuelo; Garibay-Gonzalez, Francisco; Sanchez-Monroy, Virginia; Vazquez-Zapien, Gustavo J. (Journal of Spectroscopy, 2023)
The wide range of symptoms of the coronavirus disease 2019 (COVID-19) makes it challenging to predict the disease evolution using a single parameter. Therefore, to describe the pathophysiological response to SARS-CoV-2 infection in hospitalized patients with severe COVID-19, we compared according to survival or death, the sociodemographic and clinical characteristics, the biochemical and immunological attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectra from saliva samples and their correlation with chemometric findings. Herein, we demonstrate that ATR-FTIR spectroscopy allows the description of the events related to cell damage, such as lipids biogenesis and the secondary structure of proteins associated with lactate dehydrogenase and albumin levels. Moreover, humoral (IgM) and cellular (IFN-γ, TNF-α, IL-10, and IL-6) responses were also increased in patients who died from COVID-19.